Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.actamat.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of refractory elements on Ni-excesses and Ni-depletions at γ(f.c.c.)/γ′(L12) interfaces in model Ni-based superalloys: Atom-probe tomographic experiments and first-principles calculations

Abstract: The effects of refractory (R) elements (R = Re, Ru, W, or Ta) on a base Ni-Al-Cr alloy are studied, for an aging temperature of 1073 K (800 o C) and an aging time of 256 h, employing atom-probe tomography (APT) and first-principles calculations. We find that there are strong attractive chemical binding energies between R-elements and solute (S) atoms (S = Al, Cr) in Ni-Al-Cr based alloys utilizing experimental partial radial distribution function (RDF) results, and first-principles calculations performed at 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 77 publications
(103 reference statements)
1
12
0
Order By: Relevance
“…However, with higher industrial requirements in the structure materials for high-temperature applications in aviation field, materials capable of better mechanical strength, oxidation and corrosion resistance are required. In order to improve the properties of Ni-based alloys, an excellent alternative is to alloy refractory elements [3][4][5][6]. Technologically, Cr addition could significantly improve the oxidation and hot-corrosion resistance for the nickel-based alloys by forming a stable oxidation protective layer Cr 2 O 3 at elevated temperatures [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, with higher industrial requirements in the structure materials for high-temperature applications in aviation field, materials capable of better mechanical strength, oxidation and corrosion resistance are required. In order to improve the properties of Ni-based alloys, an excellent alternative is to alloy refractory elements [3][4][5][6]. Technologically, Cr addition could significantly improve the oxidation and hot-corrosion resistance for the nickel-based alloys by forming a stable oxidation protective layer Cr 2 O 3 at elevated temperatures [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy between two doping defects at an i th NN distance is calculated by subtracting the total energy of the system with the two doping defects at the i th NN distance from the total energy of the system with the two doping defects at infinity. [19] It is given by…”
Section: Binding Energymentioning
confidence: 99%
“…[17] Yu et al [18] used transmission electron microscopy and first-principles calculations to show that Re and Ru have a strong interaction, which results in the repartitioning of Re to the γ phase. Huang et al [19] demonstrated that correlated element-element binding energies play a key role in the observed Ni retention-excesses at the γ-Ni/γ -Ni 3 Al interfaces during aging and evolution of the precipitates. In order to obtain deeper insight into the electronic mechanism of the element distribution, further theoretical calculations are needed to understand the interaction of Re element with other alloying elements at atomic-scale.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the significant influences of elemental interactions on defect-solute complexes have been highlighted in some simple systems and model alloys [20][21][22][23][24]. Compared with the strain part induced by the difference in modulus and size misfits, the electronic part resulted from d-d electronic hybridization is much more efficient in interactions between dislocations as well as vacancies and alloying solutes, especially at high temperature [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the mobility of an atom can be noticeably influenced by neighboring atoms when their interactions are strong [21]. More importantly, the attractive electronic interactions between refractory element (Re, Ru, W or Ta) and Cr can significantly influence the diffusional flux of each other during microscopic cross-diffusion process [24]. These results obtained above are quite helpful to understand the function of elemental interactions on diffusion process associated with γ′ coarsening in such a multicomponent system as Nibased SC superalloys.…”
Section: Introductionmentioning
confidence: 99%